Chronic microsporidian infection of the nasal mucosae, sinuses and conjunctivae in HIV disease. Issue 3 (June 1992) - Lacey, C J; Clarke, A M; Fraser, P; Metcalfe, T; Bonsor, G; Curry, A
Abstract : A case of chronic infection of the nasal mucosae, sinuses and conjunctivae with a microsporidian parasite in association with HIV infection and immune deficiency is reported. This microsporidian resembles both Encephalitozoon cuniculi and the newly described Encephalitozoon hellem by electron microscopy. This occurred in an adult male resident in the UK with no history of foreign travel. Although there are previous descriptions of conjunctival infections from the USA, this is the first description of infection of the nasal epithelium. Further studies are underway to classify this protozoan.